Efficacy and safety of neoadjuvant immunotherapy in resectable esophageal or gastroesophageal junction carcinoma: A pooled analysis of prospective clinical trials - Zhu, Jie; Leng, Xuefeng; Gao, Binyang; Wang, Bo; Zhang, Hanlin; Wu, Lei; Ma, Jiabao; Tan, Yan; Peng, Lin; Han, Yongtao; Wang, Qifeng (Frontiers in Immunology, 2022)
Neoadjuvant chemoradiotherapy (NCRT) plus radical esophagectomy is currently the standard treatment for resectable esophageal or gastroesophageal junction (GEJ) carcinoma. The aim of this study is to evaluate the efficacy and safety of neoadjuvant immunotherapy in resectable esophageal or GEJ carcinoma. Prospective clinical trials investigating efficacy and/or safety of neoadjuvant immunotherapy with immune checkpoint inhibitors (ICIs) followed by radical esophagectomy in patients with newly diagnosed resectable esophageal or GEJ carcinoma were identified through literature search. Quality assessment was performed by using the Newcastle–Ottawa scale. Preliminary treatment outcomes of pathologically complete response (pCR, ypT0N0) and grade 3-4 adverse effects (AEs) were pooled together and then compared with standard NCRT of the historical control CROSS study by Chi-square (χ2) test. A two-sided P value < 0.05 was considered statistically significant. A total of 17 eligible non-randomized trials with 455 participants were included into analysis. The most common primary endpoint was pCR (n = 7, 41%), and the median sample size and follow-up period was 23 patients and 7.9 months, respectively. For patients receiving neoadjuvant immunotherapy, the overall pCR, R0 resection, and grade 3-4 AE rates were 33.2%, 95.5%, and 35.1%, respectively. For esophageal squamous cell carcinoma (ESCC) and adenocarcinoma (EAC), neoadjuvant immunochemoradiotherapy showed no significant improvement in pCR rate than NCRT (ESCC, 50% vs 48.7%, P = 0.9; EAC, 32.6% vs 23.1%, P = 0.22). Grade 3-4 AEs were the most common in patients with neoadjuvant immunochemoradiotherapy, significantly higher than immunochemotherapy (46.7% vs 32.8%, P = 0.04) and NCRT (46.7% vs 18.1%, P < 0.0001). In conclusion, for patients with resectable esophageal or GEJ carcinoma, the addition of ICIs to standard NCRT could not improve pCR rate in both ESCC and EAC, but significantly increased the risk of severe AEs. Large-scale phase 3 randomized trials were urgently needed to further confirm the survival benefit and safety profile of neoadjuvant immunotherapy.